HUBUNGAN RESILIENSI DENGAN COPING STRES PADA KARYAWAN LOTTE Grosir MEDAN - Sinarsi Meliala; Laksana Tobing; Siska Dwi Ningsih; Susi Susanti Nababan (Psikologi Universitas Sari Mutiara Indonesia, 2020)
Resilience is the ability where employees can survive and rise in coping with stress. Coping is the ability to overcome self-problems from the demands of stressful situations. This study aims to determine the relationship between resilience and coping for employees of Lotte Grosir Medan. The hypothesis proposed is, there is a positive relationship between resilience and coping with employees. The sample method used is saturated samples, which amounted to 93 people or all employees with work at Lotte Grosir Medan. The measuring instrument used in this study is the scale of resilience and coping. The results of this study found resilience in employees in the high category by 71%. Coping with employees is categorized as high by 51% and the majority of employees use problem focused coping techniques by 57%. Based on the results obtained there is a positive relationship between resilience and coping for employees of Lotte Grosir Medan with a value of rxy = 0.790, meaning that the higher the resilience or ability of employee resilience, the higher the coping of Medan Lotte Wholesale employees in the face of stress.